Compota frutada de Spondias dulcis Parkinson (taperiba), Musa alinsanaya (plátano pildorita) y Myrciaria dubia (camu camu) fortificada con sangre de pollo para consumo de infantes - Arévalo Romayna, Karla María Cristina (2023)
The objective of the present study was to determine optimal production parameters of a fruit compote of Spondias dulcis Parkinson (taperiba), Musa alinsanaya (pildorita plantain) and Myrciaria dubia (camu camu) fortified with chicken blood for infant consumption. The research was quantitatively focused, using a randomized experimental design. Two formulations A and B were made with different concentrations of taperiba, plantain pildorita, camu camu and blood. The final product was characterized in terms of physicochemical, microbiological and sensory characteristics. It reported protein values of 1.35%, fat 3.50%, moisture 86.21%, ash 1.36%, carbohydrate 99.08%, and 433.2 kilocalories. Also, the presence of calcium at 8.92 mg/100g, phosphorus 20.86 mg/100g, iron 3.96 mg/100g, potassium 117.17 mg/100g, and sodium 154.43 mg/100g is evident. From the microbiological analysis, the compote showed results within the reference values, being suitable for human consumption. Sensorially, formulation B was the most acceptable in terms of odor, flavor, color and texture, demonstrating that the compote based on Amazonian fruits has optimal properties and quality for use in infant feeding.